A Test of Technical Analysis: Matching Time Displaced Generalized Patterns. Issue 2 (22nd January 2013) - Hilliard, Jimmy; Schwartz, Adam; Squire, James
<x xml:space="preserve">Abstract</x> We use a least squares metric to match the return pattern of a target stock with that of an out‐of‐sample‐twin. The twin with the smallest metric is found by a comprehensive period‐by‐period search of stocks in the Center for Research in Security Prices data set extending back to 1926. If technical analysis has value, targets of twins producing the highest returns in the twin postperiod should also have the highest performance in the target postperiod. Using a randomly selected sample of 66, 000 return patterns, we find higher means for targets corresponding to the highest returning twin quintile. We also use regressions to risk adjust target returns and find that twin returns in the postmatch period significantly predict risk‐adjusted target returns.